From Alienation to Industrialization: Hijab Activism and the Transformation of Indonesian Urban Society from Late 1970s until Today - Setiawan, Agus; Sunjayadi, Achmad; Ramlan, Yunadi; Alatas, Alwi (Journal of Al-Tamaddun, 2024)
This study aims to analyze the emergence and the dynamic development of hijab in Indonesia since the end of the 1970s. The spread of hijab was started by a few Indonesian urban Muslim women who became aware that wearing hijab is an obligation in Islamic law. They were influenced by a new wave of Islamic da’wah germinated in Indonesian urban setting. The initial use of hijab by students in public schools was seen suspiciously by the Indonesian government and was banned, causing alienation for the wearers. However, the ban was later lifted and its usage was recognized and spread in the society. The increasing number of Indonesian middle-class Muslim women who wore hijab has opened up the market for hijab industry and encouraged producers to be more creative in introducing their newest hijab products. The appearance of hijab communities, the support of the Indonesian government, and the development of online business and international halal industry in the last few years have played important roles in the rapid expansion of the industry. This study uses historical method and is strengthened by a number of primary sources, including interviews with several key players in this field. This research shows the pattern and phases of hijab transformation in the last four decades, which developed from alienation into a lucrative business and industry.